Femtosecond photodissociation dynamics of 1, 4-diiodobenzene by gas-phase X-ray scattering and photoelectron spectroscopy. (19th September 2016) - Stankus, Brian; Budarz, James M.; Kirrander, Adam; Rogers, David; Robinson, Joseph; Lane, Thomas J.; Ratner, Daniel; Hastings, Jerome; Minitti, Michael P.; Weber, Peter M.
Abstract : We present a multifaceted investigation into the initial photodissociation dynamics of 1, 4-diiodobenzene (DIB) following absorption of 267 nm radiation. We combine ultrafast time-resolved photoelectron spectroscopy and X-ray scattering experiments performed at the Linac Coherent Light Source (LCLS) to study the initial electronic excitation and subsequent rotational alignment, and interpret the experiments in light of Complete Active Space Self-Consistent Field (CASSCF) calculations of the excited electronic landscape. The initially excited state is found to be a bound 1 B1 surface, which undergoes ultrafast population transfer to a nearby state in 35 ± 10 fs. The internal conversion most likely leads to one or more singlet repulsive surfaces that initiate the dissociation. This initial study is an essential and prerequisite component of a comprehensive study of the complete photodissociation pathway(s) of DIB at 267 nm. Assignment of the initially excited electronic state as a bound state identifies the mechanism as predissociative, and measurement of its lifetime establishes the time between excitation and initiation of dissociation, which is crucial for direct comparison of photoelectron and scattering experiments.